VOICE ASSIMILATION IN MARATHI - Ari Natarina (Denpasar Institute, 2020)
This article discusses voice assimilation phenomenon in Marathi, an Indo-Aryan language. The goals of this study are three-fold: i) to provide empirical evidence for regressive assimilation in Marathi as claimed in previous studies by Junghare (1969), ii) to check whether obstruents and breathy voice can undergo and/or trigger voice assimilation, iii) to investigate what type of language Marathi belongs to based on Wetzels and MascarÃ³â€™s (2001) language typology. The results show that Marathi exhibits voice assimilation as stipulated by Junghare, and it belongs to type II languages that have voice assimilation and no word-medial and word-final devoicing.